A simple and efficient fluorescent labeling method in Staphylococcus aureus for real-time tracking of invasive bacteria - Liu, Fei; Chen, Sijie; Zou, Yingxin; Jiao, Yong; Tang, Ying (Frontiers in Microbiology, 2023)
Bacterial fluorescent labeling technology is a powerful tool for diagnosing and treating bacterial infections. Here, we present a simple and efficient labeling strategy for Staphylococcus aureus (S. aureus). Intracellular labeling of bacteria is achieved by heat shock with Cyanine NIR-I Dyes (Cy5.5@S. aureus). Several key factors such as Cy5.5 concentration and labeling time during the labeling process were systematically evaluated. At the same time, the cytotoxicity of Cy5.5 and the stability of Cy5.5@S. aureus was also evaluated by flow cytometry, inverted fluorescence microscopy, and transmission electron microscopy (TEM). In addition, Cy5.5@S. aureus was used to explore the phagocytic behavior of RAW264.7 macrophages. Results proved that Cy5.5@S. aureus had uniform fluorescence intensity and high luminance, and our method had no significant adverse effects on S. aureus compared with unlabeled S. aureus infections. Our method provides researchers with a useful option to analyze the behavior of S. aureus as an infectious agent, which can be broadly applied to study host cell-bacteria interactions on the molecular level as well as to in vivo tracing of bacterial infections.